CD93 Correlates With Immune Infiltration and Impacts Patient Immunotherapy Efficacy: A Pan-Cancer Analysis - Zhang, Zerui; Zheng, Mengli; Ding, Qiang; Liu, Mei (Frontiers in Cell and Developmental Biology, 2022)
Background: The clinical implementation of immune-checkpoint inhibitors (ICIs) targeting CTLA4, PD-1 and PD-L1 has revolutionized the treatment of cancer. However, the majority of patients do not derive clinical benefit. Further development is needed to optimize the approach of ICI therapy. Immunotherapy combined with other forms of treatment is a rising strategy for boosting antitumor responses. CD93 was found to sensitize tumors to ICB therapy after the blockade of its pathway. However, its role in immune and ICB therapy across pan-cancer has remained unexplored. Methods: In this study, we provide a comprehensive investigation of CD93 expression in a pan-cancer manner involving 33 cancer types. We evaluated the association of CD93 expression with prognosis, MMR, TMB, and MSI, immune checkpoints, methylation, TME and immune using multiple online datasets, including The Cancer Genome Atlas, Cancer Cell Line Encyclopedia, Genotype Tissue-Expression, cBioPortal, TIMER database and Tumor Immune Single-cell Hub. Results: CD93 expression varied strongly among cancer types, and increased CD93 gene expression was associated with poor prognosis as well as higher immune factors in most cancer types. Additionally, the level of CD93 was significantly correlated with MMR, TMB, MSI, immune checkpoints, methylation, TME and immune cells infiltration. Noticeably, our results mediated a strong positively contact between CD93 and CAFs, endothelial cells, myeloid dendritic cells, hematopoietic stem cells, mononuclear/macrophage subsets and neutrophil while a negative correlation with Th1, MDSC, NK and T cell follicular helper in almost all cancers. Function analysis on CD93 revealed a link between itself and promoting cancers, inflammation and angiogenesis. Conclusions: CD93 can function as a prognostic marker in various malignant tumors and is integral in TME and immune infiltration. Inhibiting of CD93 pathway may be a novel and promising strategy for immunotherapy in human cancer. Further explorations of the mechanisms of CD93 in the immune system may help improve cancer therapy methods.